2021
DOI: 10.13189/cea.2021.090530
|View full text |Cite
|
Sign up to set email alerts
|

Road Traffic Accident Data Analysis and Its Visualization

Abstract: Vehicle accidents take human life all over the world particularly in developing countries like Pakistan. It is estimated that 1.2 million people lose their lives in road accidents every year. Apart from this, 20 to 50 million are injured on a yearly basis. This annual increase in the traffic accidents trend is alarming. To bring improvement in the current road network system, the specialists need to analyze the historical data of road crashes of an area. This research aims to use the visualization technique to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…These include standard bar and column charts as well as pie charts and other graph types. Rabbani et al [24] showed how cartographic enhances the understanding of accidents for the lay person by showing them on a map projection where road accidents occur. Hotspots can easily be seen on such maps.…”
Section: E Geospatial Visualizationmentioning
confidence: 99%
See 1 more Smart Citation
“…These include standard bar and column charts as well as pie charts and other graph types. Rabbani et al [24] showed how cartographic enhances the understanding of accidents for the lay person by showing them on a map projection where road accidents occur. Hotspots can easily be seen on such maps.…”
Section: E Geospatial Visualizationmentioning
confidence: 99%
“…Python ML packages include scikit-learn, also known as sklearn. These libraries are generally open source and are regularly updated and enhanced by their user communities to provide the latest features [24].…”
Section: F Python Library Approachmentioning
confidence: 99%
“…More importantly, the paper provides an evidence-based approach to the development of the tool that includes use of visualization and processing techniques that have been shown to be easy to use by the broader public. The iterative development of saferoadmaps (SRM) is described in [17]. SRM was designed to focus on transportation safety and provide a means of visual communication, with the potential to raise user awareness and impact driving behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Authors suggested the remedial measures be followed on various categories of roads in India to achieve road safety. Rabbani et al [ 15 ] presented the statistical analysis of crash data in Peshawar, Pakistan, and stated the importance of crash data analysis to achieve road safety. Authors have found that the majority of crashes took place in daytime, and the 30–45 years age group was involved in majority of the road crashes.…”
Section: Introductionmentioning
confidence: 99%